PENGEMBANGAN ADJUSTABLE WHEELCHAIR UNTUK OPTIMALISASI PROSES BELAJAR ANAK CEREBRAL PALSY DI SLB YPAC SUMATERA BARAT - Aziza Azarah; Setia Budi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the problems found in SLB YPAC West Sumatra. There is a girl with the initials K who has physical and motoric problems. This condition is further exacerbated by the lack of ergonomic learning aids, such as wheelchairs that cannot be adjusted to the needs of the user. This study aims to develop an adjustable wheelchair that supports the optimization of the learning process for children with cerebral palsy at SLB YPAC West Sumatra. The method used is Research and Development (R&D) with the Successive Approximation Model (SAM) approach, through three stages, namely preparation, iterative design, and iterative development. The trial subjects included disability experts, design experts, engineering experts, and one cerebral palsy student as a user. Data collection was carried out through observation, interviews, documentation, and validation questionnaires and practicality tests. The validation results from the experts showed that the feasibility level was 87% with the category